Funciones psíquicas de las marcas corporales (2010)
ABSTRACT: This article shows the results of a research titled Funciones psíquicas de las marcas corporales (Psychic Functions of Body Marking) that analyses the tattoo, scarification and piercing boom in teenagers and young people. Its aim is to elucidate the body statute in our days. From the acknowledgment of the changes in status of human body throughout history and in different cultures, we investigate the special psychic functions of those practices and their symbolic implications, by using some psychoanalytical theories about body image and adolescence.